METHODS OF TEACHING RUSSIAN LANGUAGE (Archive of Conferences, 2021)
Language is one of the most interesting communication tools in the hands of people. To use a language well, you need to research language features and details (Egorova, 2008). The methodology is designed to explore the language concept and analytical skills of the student. The methodology is designed to explore the student's feelings of language and analytical skills. (Lvov, 2007). Linguistic analysis ensures that the difference between language levels is respected (Galai, 2012). The methodology also affects the level of knowledge and skills of students.